PENGARUH TEKNIK ASSERTIVE TRAINING UNTUK MENINGKATKAN KOMPETENSI SOSIAL SISWA DI SMP MUHAMMADIYAH 1 PEKANBARU - Siti Hutami; Elni Yakub; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Social competence is an effective response from someone to various life situations or the ability to interact effectively with the environment. This study aims to determine the effect of assertive training techniques on improving social competency of students in Pekanbaru Muhammadiyah 1 Middle School. This type of research uses quantitative research with an experimental method using the One-Group Pretest-Posttest Design research design. The measuring instrument used in this study is a social competency measurement scale consisting of 38 item statements. The subjects of this study were 7 students who had low social competence. The data analysis technique used is non-parametric statistical techniques using Wilcoxon analysis test. The results of the study prove that the research hypothesis is accepted. This is known from